1993
DOI: 10.1161/01.hyp.21.4.442
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme variability in hypertensive and normotensive rats.

Abstract: Recent data have revealed biological and genetic variability in normotensive Wistar-Kyoto rats, which are considered to be the most appropriate control strain for spontaneously hypertensive rats. To investigate the possibility that angiotensin converting enzyme activity could be affected by this variability, we measured plasma and tissue (lung, heart, renal cortex, renal medulla, and adrenal gland) angiotensin converting enzyme activity in spontaneously hypertensive rats and normotensive Wistar-Kyoto rats from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Based on these results, we carried out the present work to evaluate the relevance of vascular ACE for the development of hypertension in these rats. A recent report shows that the ACE activity differs considerably between various colonies of SHR and WKY rats but not within a strain from a single stock, 20 so the animals used for this study were obtained from the same colony investigated in the previous linkage studies. 8 "…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, we carried out the present work to evaluate the relevance of vascular ACE for the development of hypertension in these rats. A recent report shows that the ACE activity differs considerably between various colonies of SHR and WKY rats but not within a strain from a single stock, 20 so the animals used for this study were obtained from the same colony investigated in the previous linkage studies. 8 "…”
Section: Discussionmentioning
confidence: 99%
“…In the control low-flow experiments (n ϭ 6, Sprague-Dawley rats, 8 -9 mo old), hearts were perfused in the CF mode throughout the experiment. The use of the Sprague-Dawley strain as the control for SHR myocardial studies (in some cases, preferred over the WKY strain) has been previously reported (14,47). Before the perfusion experiment, heart weight was estimated from rat body weight.…”
Section: Methodsmentioning
confidence: 99%